2007
DOI: 10.1002/jbm.a.31566
|View full text |Cite
|
Sign up to set email alerts
|

A novel multiphase anodic spark deposition coating for the improvement of orthopedic implant osseointegration: An experimental study in cortical bone of sheep

Abstract: The effect of a new three-step anodic spark deposition process, labeled TiSpark, including two consecutive treatments performed first in a P solution and second in Ca solution, followed by an additional alkali etching step, was investigated for the improvement of osseointegration of commercial grade 2 titanium, machined (Ti) or Al(2)O(3) sandblasted (Ti-SA), cylindrical implants (12 mm in length and 4 mm in diameter) in cortical bone of 12 adult sheep. Histomorphometric and microhardness measurements were carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 36 publications
3
30
0
Order By: Relevance
“…These results are in agreement with previously published data [30,[35][36][37][38], although a direct comparison is not appropriate due to differences in animal models, experimental methods, surgical procedures and experimental times. For example, Chiesa et al [30], in a study on the fixation dynamics of spark modified and control titanium in sheep, demonstrated a statistically significant increase in the bone-implant contact for spark titanium at 4 and 8 weeks, but saw no statistically significant differences at 12 weeks.…”
Section: Discussionsupporting
confidence: 95%
See 4 more Smart Citations
“…These results are in agreement with previously published data [30,[35][36][37][38], although a direct comparison is not appropriate due to differences in animal models, experimental methods, surgical procedures and experimental times. For example, Chiesa et al [30], in a study on the fixation dynamics of spark modified and control titanium in sheep, demonstrated a statistically significant increase in the bone-implant contact for spark titanium at 4 and 8 weeks, but saw no statistically significant differences at 12 weeks.…”
Section: Discussionsupporting
confidence: 95%
“…Previous studies evaluated the osteointegrative potential of these surfaces in the rat and the sheep by means of histology and static histomorphometry at time points between 4 and 12 weeks after surgery [30,[35][36][37][38]. Pertaining to the in vivo performance of these surfaces, the present work aims to evaluate the osteogenic primary response to implanted surfaces using a short (within 4 weeks) experimental time frame.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations